Perceived Barriers and Enablers of Help-Seeking for Substance Use Problems During Adolescence. Issue 1 (January 2018) - Berridge, Bonita J.; McCann, Terence V.; Cheetham, Ali; Lubman, Dan I.
Aim. Receiving professional help early can reduce long-term harms associated with substance use. However, little is known about the factors that influence help-seeking for substance use problems during early-mid adolescence, prior to the emergence of disorder. Given that beliefs regarding help-seeking are likely to develop early, understanding adolescent views of help-seeking during this period is likely to provide important information for prevention and intervention efforts. The current study identifies perceptions that would facilitate or prevent adolescents from seeking support for substance use problems from formal and informal help sources. Method. Thirty-four 12- to 16-year-olds from two schools in Melbourne, Victoria, Australia, were recruited. A qualitative interpretative design was used, incorporating semistructured, audio-recorded interviews. Results. Three overlapping themes that reflected barriers or enablers to help-seeking were identified: approachability, confidentiality and trustworthiness, and expertise. Help-seeking was facilitated when adolescents believed that the help source would be supportive and understanding, would keep information confidential, and had expertise in the alcohol and drug field. Conversely, adolescents were reluctant to seek help from sources they believed would be judgmental, lacked expertise, or would inform their parents. Conclusions. These findings highlight perceptions that may influence help-seeking for alcohol and drug problems during adolescence. Further research is needed to determine if help-seeking can be facilitated by improving parents' and peers' knowledge and promoting health professionals' expertise in working with young people's alcohol and drug issues.